Enabling financial literacy in deprived communities in South Africa - Ramoenyane, Keorapetse Phemelo Johannes (My University, 2018)
The purpose of the research is to understand and test the relationship between financial literacy and social entrepreneurship and whether there is a positive impact that could be derived from the relationship. The aim of the research was to determine examine how can social entrepreneurship enable financial literacy within the Diepsloot Community in South Africa? The motive and rationale to pursue analyse a social entrepreneurship project and seek to understand solutions that could aid in combating poverty and inequality and to harness and promote financial inclusion as well as financial literacy to the marginalised members of society. A qualitative research methodology was utilised to collect non-numerical data and reviewed to understand the impact on the recipients of the financial literacy booklets as well as documenting the business case of the social enterprise. A sample of community members was utilised to collect data and conduct the research. Limitations to the study include a narrow sample of participants as well as a narrow demographic. Recommendations of the research present alternative solutions that could aid at facilitating the rate of financial transformation. The conclusion of the report suggest that social entrepreneurship could be used as a model to disburse financial literacy even at early childhood development.
MBA
Keywords: Financial literacy. Consumer education. Finance, Personal -- Study and teaching -- South Africa.